2011
DOI: 10.1248/bpb.34.1373
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Attention-Deficit/Hyperactivity Disorder

Abstract: Attention-deficit hyperactivity disorder (AD/HD) is a clinically heterogenous disorder including hyperactivity, impulsivity, and inattention. Both psychostimulant and non-psychostimulant drugs such as methylphenidate and atomoxetine, respectively, to modulate catecholeamine neurotransmission are used as current pharmacotherapies for AD/HD. Multiple lines of evidence suggest that genetic factors play major roles in the etiology of AD/HD. meta-Analyses and pooled data analyses have suggested associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…A similar observation has been made for coloboma mice (42), an established ADHD model (43,44). Together, the neurobehavioral defects of ACC mice strongly resemble the symptoms observed in patients with ADHD (1).…”
Section: Discussionsupporting
confidence: 53%
“…A similar observation has been made for coloboma mice (42), an established ADHD model (43,44). Together, the neurobehavioral defects of ACC mice strongly resemble the symptoms observed in patients with ADHD (1).…”
Section: Discussionsupporting
confidence: 53%
“…Even though there are numerous reviews of candidate animal models for ADHD (Arime et al, 2011;Leo and Gainetdinov, 2013), to our knowledge, there are no reviews of the contribution of other methods, e.g., in silico models.…”
Section: Fig 3: Density Vs Number Of Citations By Human Papersmentioning
confidence: 99%
“…To date, SHRs have been the most commonly investigated animal model and studies have found links between ADHD-like behaviors and impaired dopamine release in the prefrontal cortex, nucleus accumbens and striatum [33] . The locus coeruleus-norepinephrine system, which is thought to be responsible for optimizing arousal and facilitating sustained attention, is also impaired in SHRs, supporting the theory that inattention in ADHD is related to hypoarousal and problems with alerting attention [14,34,35] .…”
Section: Neurophysiological Studiesmentioning
confidence: 99%